Entrepreneurship and intrapreneurship in social, sustainable, and economic development - Sebastian Aparicio; Andreu Turro; María Noguera (MDPI, 2020)
Entrepreneurship and intrapreneurship have become a vehicle that offers solutions for social, environmental, and economic problems. Even though the level of entrepreneurial activity and its diversity have been motivated through public policies, social support has also played an important role in encouraging people to think of entrepreneurship as a desirable career choice. This book brings together analyses of those elements required for entrepreneurial and intrapreneurial intention and action, which ultimately become important leverages of development. Chapters highlight the importance of rural, urban, university, organizational, and family environments for a bunch of intentions and behaviors such as green, sport, social, corporate, innovative, traditional, and gender entrepreneurship. This entrepreneurial diversity is translated into higher development through the empowerment of women, environmental consciousness, and efficient production. Policymakers, scholars, and practitioners can find different examples and cases useful for decision-making, learning, and practice in this book.
Keywords: 650; entrepreneurial activity; intrapreneurship; gender; institutions; sustainable entrepreneurship; national growth; regional development